Q. 14.1( 123 Votes )

# Prove the followi

Answer :

LHS = sec4x – sec2x

= (sec2x) 2 – sec2x

We know sec2 θ = 1 + tan2 θ.

= (1 + tan2x) 2 – (1 + tan2x)

= 1 + 2tan2x + tan4x – 1 - tan2x

= tan4x + tan2x = RHS

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Find the values oRD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

The value of sin Mathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

If 12 sin x – 9 sRD Sharma - Mathematics

Write the intervaRD Sharma - Mathematics